2007
DOI: 10.1098/rsta.2007.2043
|View full text |Cite
|
Sign up to set email alerts
|

Marine aerosol production: a review of the current knowledge

Abstract: The current knowledge in primary and secondary marine aerosol formation is reviewed. For primary marine aerosol source functions, recent source functions have demonstrated a significant flux of submicrometre particles down to radii of 20 nm. Moreover, the source functions derived from different techniques up to 10 mm have come within a factor of two of each other. For secondary marine aerosol formation, recent advances have identified iodine oxides and isoprene oxidation products, in addition to sulphuric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
582
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 665 publications
(612 citation statements)
references
References 79 publications
(105 reference statements)
24
582
3
3
Order By: Relevance
“…Bacterial processes appeared to play only a minor role in the reduction of iodate to iodide. Leeuw 2007). In coastal regions, I 2 can also directly be released into the atmosphere by kelp and seaweed and reacts here to equally form IO.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial processes appeared to play only a minor role in the reduction of iodate to iodide. Leeuw 2007). In coastal regions, I 2 can also directly be released into the atmosphere by kelp and seaweed and reacts here to equally form IO.…”
Section: Introductionmentioning
confidence: 99%
“…Sea-salt aerosol is emitted from the sea surface, through bubble-bursting processes resulting in sea-spray particles with sizes ranging from submicrometre to a few micrometres (O'Dowd and de Leeuw, 2007). Sea-salt aerosols play an important role in atmospheric chemistry, providing the surface for heterogeneous reactions and acting as a sink for anthropogenic and natural gaseous pollutants (Tsyro et al, 2011).…”
mentioning
confidence: 99%
“…Traces of syringic acid (SyA), homovanillic acid (HA) and syringaldehyde (SyAH) represented 1% of the total concentration of PC in the aerosol samples collected in 2014e2015. The concentrations were similar in 2010e2011 , where the ocean was suggested as a possible local source of PC by ejecting fine particles (<1 mm) containing organic compounds into the atmosphere (O'Dowd and De Leeuw, 2007). For the 2014e2015 samples evaluated in the present research, the same source can also be suggested and biomass burning can be excluded as the main source of PC.…”
Section: Phenolic Compounds (Pc) In Pm 10mentioning
confidence: 51%